ANALISIS FAKTOR YANG MEMENGARUHI MINAT TOKO MENGGUNAKAN E-MARKET PLACE BUILDING MATERIAL UNTUK PENJUALAN BERBASIS APLIKASI - Aditya Narendra Wardhana; Mirza May Jayanti; Ilmanza Restuadi Kurniawan (Politeknik Ubaya, 2019)
This research has the basic purpose of finding the impact of Building Material Store Characteristics, Environmental Competitiveness and Promotion or support from Decision Maker to the interest/willingness of using E-Marketplace Building Material Semen Indonesia that defined as purchase intention in partially This research is a quantitative research. Data collection techniques used in this study is a questionnaire method with a likert scale of 1-7. The data analysis used is descriptive statistical data analysis method and to know what factors influence the interest/willingness of Store Owner in using E-Marketplace Building Material Semen Indonesia used multiple linear regression analysis. The results of this study indicate that the Building Material Store Characteristics, Environmental Competitiveness and Support from Decision Maker influence the interest/willingness of using E-Marketplace Building Material PT. Semen Indonesia that defined as purchase intention partially.